The Function of the HGF/c-Met Axis in Hepatocellular Carcinoma - Wang, Haiyu; Rao, Benchen; Lou, Jiamin; Li, Jianhao; Liu, Zhenguo; Li, Ang; Cui, Guangying; Ren, Zhigang; Yu, Zujiang (Frontiers in Cell and Developmental Biology, 2020)
Hepatocellular carcinoma (HCC) is one of the most common malignancies worldwide, leading to a large global cancer burden. Hepatocyte growth factor (HGF) and its high-affinity receptor, mesenchymal epithelial transition factor (c-Met), are closely related to the onset, progression and metastasis of multiple tumors. The HGF/c-Met axis is involved in cell proliferation, movement, differentiation, invasion, angiogenesis and apoptosis by activating multiple downstream signaling pathways. In this review, we focus on the function of the HGF/c-Met axis in HCC. The HGF/c-Met axis promotes the onset, proliferation, invasion and metastasis of HCC. Moreover, it can serve as a biomarker for diagnosis and prognosis, as well as a therapeutic target for HCC. In addition, it is closely related to drug resistance during HCC treatment.